Tracking von Menschen und menschlichen Zuständen - Dunau, Patrick (Karlsruher Schriften zur Anthropomatik, 2021)
This work evaluates different approaches for observing human states. The considered human conditions comprise the current position, the actual performance, and the emotional facial expression. This work relies on tracking and static classification methods to observe the humans' conditions.